WhatsApp, Viber and Telegram which is Best for Instant Messaging? - Tole Sutikno; Lina Handayani; Deris Stiawan; Munawar Agus Riyadi; Imam Much Ibnu Subroto (Institute of Advanced Engineering and Science, 2016)
There are many free instant messengers available now which allow to communicate with friends with text, phone call, video, sharing of files, in group or not and keep contact with them even internationally. But only very few of the instant messengers have gained a popularity and attention. Recent studies have shown that the most popular instant messengers are WhatsApp, Viber and Telegram. Even, Facebook acquired WhatsApp due to have huge users. Viber is another messenger with many integrated features that allows the phone calls and sends the text messages for free and there is no subscription like WhatsApp. While Telegram offers the users an open-source platform with no ads, a clean fast interface, asks for no payments whatsoever and the biggest selling point is security. WhatsApp, Viber and Telegram which instant messenger is best? The popularity of Telegram has reached at the top of Google play store and become the most downloaded messaging app in the world today. But at the moment WhatsApp is still the winner!